Study on the effect of optimized Traditional Chinese Medicine nursing plan on defecation of patients after surgical treatment of mixed hemorrhoids - ZHOU, Yuzhen; XIE, Liping (Chinese Journal of Integrative Nursing, 2023)
Objective To investigate the effect of optimized Traditional Chinese Medicine(TCM) nursing plan on defecation of postoperative patients with surgical treatment of mixed hemorrhoids. Methods Expert consultation, Delphi method and document retrieval were used to optimize the TCM nursing program. Totally 416 patients with hospital admission date form January and December 2021 were included as control group, receiving standard nursing plan. Another 393 patients with hospital admission date form January and December 2022 were recruited as the study group, received optimized TCM nursing plan. Defecation condition at third day and fifth day after surgery, hospitalization cost of the patient and score of TCM nursing quality assessment were compared between groups. Results The score of Wexner Constipation Scoring System in the study group was lower than that in the control group at third day and fifth day after surgery (P＜0. 01). The hospitalization cost of the patient in the study group were less than that in the control group(P＜0. 01). The score of TCM nursing quality assessment in the study group was higher than that in the control group(P＜0. 05). Conclusion The optimized TCM nursing plan is effective to prevent postoperative constipation in patients with surgical treatment of mixed hemorrhoids. (目的 对混合痔中医护理方案进行优化, 探讨优化后的方案对患者术后排便功能的改善效果。方法 采用专家咨询、德尔菲法、文献查找等方法对混合痔中医护理方案中的护理措施进行优化。通过病例回顾的方法选取2021年1月—12月住院的患者416例为对照组, 按照标准方案进行护理; 将2022年1月—12月收治的患者393例纳入研究组, 按优化后的中医护理方案进行护理。对比两组患者术后第3天、第5天的排便功能, 统计住院费用, 评价护士中医护理工作质量。结果 研究组术后第3天、第5天Wexner便秘评分系统得分低于对照组, 差异有统计学意义(P＜0. 01)。研究组住院费用低于对照组, 差异有统计学意义(P＜0. 01)。研究组护士中医护理工作质量评分高于对照组, 差异有统计学意义(P＜0. 05)。结论 优化后的混合痔中医护理方案有效预防术后便秘的发生。)